2018
DOI: 10.1371/journal.pbio.2005164
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution frequency tuning but not temporal coding in the human cochlea

Abstract: Frequency tuning and phase-locking are two fundamental properties generated in the cochlea, enabling but also limiting the coding of sounds by the auditory nerve (AN). In humans, these limits are unknown, but high resolution has been postulated for both properties. Electrophysiological recordings from the AN of normal-hearing volunteers indicate that human frequency tuning, but not phase-locking, exceeds the resolution observed in animal models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 45 publications
5
46
0
Order By: Relevance
“…This conclusion is 285 consistent with other studies showing that pitch perception is possible even with spectrally 286 resolved harmonics that are too high in frequency to elicit phase locking (Oxenham et al, 2011;287 Lau et al, 2017). In addition, the fact that timing fidelity in the human auditory nerve is no 288 greater than that found in smaller mammals (Verschooten et al, 2018), supports our conclusion 289 that differences in pitch perception between humans and other mammals cannot be ascribed to 290 differences in timing fidelity and phase locking, but instead may be due to differences in the 291 sharpness of cochlear tuning. 292 293…”
Section: Effects Of Hearing Loss On Masking Functions 117supporting
confidence: 66%
“…This conclusion is 285 consistent with other studies showing that pitch perception is possible even with spectrally 286 resolved harmonics that are too high in frequency to elicit phase locking (Oxenham et al, 2011;287 Lau et al, 2017). In addition, the fact that timing fidelity in the human auditory nerve is no 288 greater than that found in smaller mammals (Verschooten et al, 2018), supports our conclusion 289 that differences in pitch perception between humans and other mammals cannot be ascribed to 290 differences in timing fidelity and phase locking, but instead may be due to differences in the 291 sharpness of cochlear tuning. 292 293…”
Section: Effects Of Hearing Loss On Masking Functions 117supporting
confidence: 66%
“…Early in the study of the efficient coding of speech using ICA, a parallel was drawn between the theoretical optimal decomposition of speech and cochlear tuning [11]. Estimates of the frequency selectivity of the inner ear based on physiological measurements in mammals are consistent with the power law model used in this work [35,36]. The exponent is about the same than for ICA filters, although slightly lower (0.6 compared to 0.7-0.8).…”
Section: Agreement With the Efficient Coding Hypothesis And Cochlear supporting
confidence: 63%
“…The specificity of human auditory tuning is still a subject of controversy. While it has been argued that it is not very different from unspecialized mammals [38], there is increasing evidence that frequency selectivity is significantly higher in humans [36,39], especially in response to low intensity sounds [40]. Lewicki also suggested that an explanation for the median β value is the right balance between transient and sustained sounds in speech.…”
Section: Agreement With the Efficient Coding Hypothesis And Cochlear mentioning
confidence: 99%
“…Second, scaling symmetry, a key principle commonly evoked in modeling cochlear mechanics, appears to break down below 1–1.5 kHz ( van der Heijden and Joris, 2006 ; Abdala et al, 2011) . Third, various neurophysiological measures [e.g., van der Heijden and Joris (2006) ; Verschooten et al (2018) ] suggest auditory nerve responses encode information differently between base and apex, with a steep drop in the ability to encode timing information above 1–2 kHz ( Verschooten et al, 2018) . Fourth, it is well known that harmonic components of perceived pitch transition from resolved to unresolved around 1–2 kHz ( Plack et al, 2006) .…”
Section: Discussionmentioning
confidence: 99%